ANALYSIS OF THE DIRECT CASH TRANSFER (BLT) PROGRAM POLICY AND ITS IMPLICATIONS FOR THE WELFARE OF POOR HOUSEHOLDS IN DISADVANTAGED AREAS OF EAST NUSA TENGGARA PROVINCE - Marthen Lona (Adisam Publisher, 2026)
The Direct Cash Transfer (BLT) Program is a social protection policy instrument aimed at reducing poverty levels, particularly in disadvantaged regions such as East Nusa Tenggara Province. This study seeks to analyze the BLT policy and examine its implications for the welfare of poor households using a qualitative approach based on library research. The data are derived from various scientific literature and official documents, which are analyzed using content analysis techniques. The findings indicate that the BLT program contributes positively to the fulfillment of basic needs and helps maintain household economic stability in the short term. However, its effectiveness in promoting long-term welfare improvement remains limited. Thus, BLT can be considered an effective instrument for short-term poverty alleviation; however, it requires synergy with economic empowerment programs to generate sustainable welfare impacts.